Effect of arsenic on Amaranthus gangeticus (Bangladesh Journal of Scientific and Industrial Research, 2018)
Groundwater arsenic contamination has become a threat to the crop production potential in the soils of vast areas of Bangladesh. Situation is grave in some districts of the country, particularly the southern part. A pot experiment was conducted to investigate the effects of arsenic treated irrigation water (0, 1, 2, 5 and 10 mgL-1), where a total of ten (10) irrigations were provided thus the treatments received 0, 10, 20, 50, and 100 mg arsenic (As) pot-1. Effects of applied levels of arsenic on Amaranthus gangeticus (Lal shak) were evaluated in terms of the growth, yield, major nutrients’ content, and their translocation in the plant. As treatments significantly reduced (p≤0.05) the dry weight of shoot and root by 19.31% and 44.03% respectively. Both total and available concentrations of nitrogen (N), potassium (K) and sulfur (S) were significantly (p≤ 0.05) suppressed by the As treatments, while only higher three doses significantly (p≤ 0.05) affected both levels of concentrations of phosphorus (P), calcium (Ca) and magnesium (Mg). Translocation coefficients for soil to root for P, K, S, and Mg were significantly reduced (p≤ 0.05), while translocation coefficients for root to shoot were significantly increased (p≤ 0.05) for K and S by 5 and 10 mgL-1 of arsenic treatments.Bangladesh J. Sci. Ind. Res.53(4), 259-264, 2018